An intrinsic, label-free signal for identifying stem cell-derived cardiomyocyte subtype. (9th December 2019) - Chang, Che-Wei; Kao, Hillary K. J.; Yechikov, Sergey; Lieu, Deborah K.; Chan, James W.
Abstract: Human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes have many promising applications, including the regeneration of injured heart muscles, cardiovascular disease modeling, and drug cardiotoxicity screening. Current differentiation protocols yield a heterogeneous cell population that includes pluripotent stem cells and different cardiac subtypes (pacemaking and contractile cells). The ability to purify these cells and obtain well-defined, controlled cell compositions is important for many downstream applications; however, there is currently no established and reliable method to identify hiPSC-derived cardiomyocytes and their subtypes. Here, we demonstrate that second harmonic generation (SHG) signals generated directly from the myosin rod bundles can be a label-free, intrinsic optical marker for identifying hiPSC-derived cardiomyocytes. A direct correlation between SHG signal intensity and cardiac subtype is observed, with pacemaker-like cells typically exhibiting ~70% less signal strength than atrial- and ventricular-like cardiomyocytes. These findings suggest that pacemaker-like cells can be separated from the heterogeneous population by choosing an SHG intensity threshold criteria. This work lays the foundation for developing an SHG-based high-throughput flow sorter for purifying hiPSC-derived cardiomyocytes and their subtypes. : Abstract : Myosin filaments are second harmonic generation (SHG) active cellular components that can combine two incident photons and emit a new photon with twice of the energy of an initial photon. The SHG signal is specific to stem cell-derived cardiomyocytes and its signal strength can be used to identify cells by maturity and separate cells by subtype.